Transformasi Sistem Informasi Akuntansi di Era Artificial Intelligence dan Big Data: Sebuah Tinjauan Literatur Deskriftif-Konseptual - Muhammad Arif Siagian; Randa Yosua Sinaga (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
The rapid advancement of digital technology in the era of Industrial Revolution 4.0 and Society 5.0 has triggered a massive explosion of data volume (Big Data) and the widespread adoption of Artificial Intelligence (AI) across various sectors, including accounting. This study aims to analyze in depth the transformation of Accounting Information Systems (AIS) resulting from the integration of AI and Big Data, and to formulate a future AIS conceptual framework. Employing a qualitative method with a descriptive-conceptual literature review design, this research synthesizes various relevant scientific literatures, regulations, and previous studies from recent years. The findings indicate that AI and Big Data have shifted the conventional AIS paradigm—which originally focused on periodic, historical-monetary data recording—into a system that is adaptive, predictive, and capable of processing non-financial data in real-time. This transformation significantly impacts AIS components, ranging from data entry automation, enhanced software capabilities, to the reconstruction of internal controls based on automated fraud detection. Conceptually, the role of accountants is reoriented from mere bookkeepers to strategic data analysts. The implications of this study emphasize the urgency of adapting accounting education curricula and ensuring organizational technology infrastructure readiness to optimize the potential of modern AIS.